2019
DOI: 10.1002/ardp.201900063
|View full text |Cite
|
Sign up to set email alerts
|

Design, synthesis, and molecular docking studies of novel pyrazolyl 2‐aminopyrimidine derivatives as HSP90 inhibitors

Abstract: A series of novel pyrazolyl 2‐aminopyrimidine derivatives (7a‐t) were designed based on scaffold hopping techniques, synthesized and biologically evaluated for their HSP90 inhibition and anticancer activity. Several compounds exhibited potent HSP90 inhibition with IC50 values less than that of the reference standard 17‐AAG (1.25 µM). The most potent compound 7t displayed excellent HSP90 inhibition with an IC50 of 20 nM and in vitro antiproliferative potential against three cancer cell lines (IC50 < 5 µM). 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…In 2019, Mettu et al designed and synthesised novel pyrazolyl 2-aminopyrimidine derivatives ( Figure 5(h) ) as HSP90 inhibitors, which were evaluated using molecular docking studies [ 142 ]. The studies showed that synthesised molecules retained all the essential binding interactions with HSP90 [ 142 ].…”
Section: Molecular Reactivity Allosteric Dynamics and Allosteric Designmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2019, Mettu et al designed and synthesised novel pyrazolyl 2-aminopyrimidine derivatives ( Figure 5(h) ) as HSP90 inhibitors, which were evaluated using molecular docking studies [ 142 ]. The studies showed that synthesised molecules retained all the essential binding interactions with HSP90 [ 142 ].…”
Section: Molecular Reactivity Allosteric Dynamics and Allosteric Designmentioning
confidence: 99%
“…In 2019, Mettu et al designed and synthesised novel pyrazolyl 2-aminopyrimidine derivatives ( Figure 5(h) ) as HSP90 inhibitors, which were evaluated using molecular docking studies [ 142 ]. The studies showed that synthesised molecules retained all the essential binding interactions with HSP90 [ 142 ]. In another study in 2019, Rampogu et al focused on natural compounds as possible inhibitors of HSP90 for breast cancer-pharmacophore-guided molecular modeling [ 143 ].…”
Section: Molecular Reactivity Allosteric Dynamics and Allosteric Designmentioning
confidence: 99%
“…Among them, compound 56e established the highest binding affinity to Hsp90 (20 nM) with anti-proliferative function against MCF7 (IC50 = ~2.4 µM), MDA-MB-231 (IC50 = ~0.8 µM), and HCT-116 (IC50 = ~4.8 µM), in vitro. According to Western blotting (WB) analysis, two compounds ( 56b , 56e ) generated dose-dependent degradation of two client proteins (pHER2 and pERK1/2) [ 152 ]. Molecular docking studies demonstrated that the compounds 56b – 56e were significant Hsp90 inhibitors.…”
Section: Hsp90 Inhibitorsmentioning
confidence: 99%
“…These studies revealed that the para substitution on pyrazole rings A and B, especially with the p-nitro group on ring B and 2 amino groups on the pyrimidine ring, had unique consequences on the development of new Hsp90 inhibitors. The binding potential of the disubstituted pyrazolyl pyrimidine scaffold and pocket of Hsp90 had effective interactions with Thr184, Asn51, and AsH93 (a protonated form of Asp93), Asp54, and Lys58 [ 152 ]. According to the results reported by Mettu et al compound 56e was the most active compound; the apoptosis potential of this compound was recognized by the Annexin V assay, where it could induce mitochondrial stress that increases membrane permeability, causing induction of apoptosis in MCF-7 cells.…”
Section: Hsp90 Inhibitorsmentioning
confidence: 99%